1985
DOI: 10.1210/endo-117-5-1772
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Adrenal Renin-Angiotensin System in the Regulation of Potassium-Stimulated Aldosterone Production*

Abstract: Potassium is a major regulator of aldosterone production. It also increases adrenal renin. The causal relationship between potassium and adrenal renin is not known. To evaluate the role of the intraadrenal renin-angiotensin (ANG) system in potassium-stimulated aldosterone synthesis and release, specific adrenal renin activity, PRA, and plasma aldosterone were measured during potassium loading or captopril treatment in the rat. Adrenal ANGs were determined using a HPLC system combined with RIA to obtain quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…Studies on the interaction of adrenal renin and aldosterone have demonstrated the presence of adrenal tissue angiotensin I, II, III and angiotensinogen (Nakamura et al, 1985, Ganten et al, 1976, Mendelsohn 1984. The findings obtained support the concept of a local system for the renin-angiotensinaldosterone axis.…”
Section: Disc Nssionsupporting
confidence: 52%
See 3 more Smart Citations
“…Studies on the interaction of adrenal renin and aldosterone have demonstrated the presence of adrenal tissue angiotensin I, II, III and angiotensinogen (Nakamura et al, 1985, Ganten et al, 1976, Mendelsohn 1984. The findings obtained support the concept of a local system for the renin-angiotensinaldosterone axis.…”
Section: Disc Nssionsupporting
confidence: 52%
“…Accumulated results of studies on adrenal renin have suggested that this enzyme is closely related to aldosterone release (Doi et al, 1984, Nakamura et al, 1985. However, the mechanism by which adrenal renin controls aldosterone release is unclear.…”
Section: Disc Nssionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the potassium ions accumulated following nephrectomy may stimulate vascular renin production as demonstrated in adrenal renin which is increased after potassium loading in the presence of a suppressed plasma renin level (Nakamaru et al, 1985). Thirdly, a role of the sympathetic nerve activation in the stimulation of vascular ANG II generation (Nakamura et al, 1986) following nephrectomy has yet to be proven.…”
Section: Discussionmentioning
confidence: 99%